ANALISA FAKTOR-FAKTOR YANG MEMOTIVASI PEREMPUAN BERWIRAUSAHA MELALUI BISNIS ONLINE (Studi Kasus Pada Ibu Muda di Kecamatan Bangkalan) - Anugrahini Irawati, S; Sudarsono, Bambang (Distribusi - Journal of Management and Business, 2018)
The role of women in the business world needs to be considered, especially in the field of entrepreneurship. Technological developments in this case Information Technology can help simplify in conducting business activities known as online business. Online business activities help create new fields and job opportunities and help the family economy in particular. Most women who use the Internet as an opportunity to open jobs and fill their spare time in this case young mothers. The purpose of this research is to know the factors that motivate women entrepreneurship through online business. The population in this study are young mothers of Bangkalan subdistrict who have an online business. This research is a quantitative research. Sample collection was done by distributing questionnaires, using nonprobability sampling method with purposive sampling technique to 75 young mothers who do business online. To find out what factors motivate women entrepreneurship through online business then researchers use descriptive qualitative research methods. The results showed that there are six factors that are formed in motivating women entrepreneurship through online business especially in young mothers are family factor, Self Interest, Employment Opportunities, Technical Knowledge, Entrepreneurial Experience, Family Background, Market Potencial. Keywords: Factor Analysis, Motivation, Entrepreneurial Woman, Online Business